2010
DOI: 10.1177/0271121410371986
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention Providers’ Perspectives About Implementing Participation-Based Practices

Abstract: Early intervention providers submitted videotapes of home visits as part of requirements for a professional development course. Taped visits were classified into two practice groups: providers who demonstrated use of participation-based practices and those who did not (i.e., traditional practices). A sample of providers, selected from each of these groups, were interviewed to elicit perspectives about implementing participation-based practices. Findings indicate that providers, regardless of practice classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 28 publications
4
80
1
1
Order By: Relevance
“…Department of Health & Human Services, 2004). For example, some home visitors may have some family-centered attitudes, yet struggle to see their role as one of promoting positive parenting instead of as one who teaches the child themselves-a far less effective practice (Bruder, 2010;Campbell & Sawyer, 2007Fleming, Sawyer, & Campbell, 2011;Hebbeler & Gerlach-Downie, 2002;Peterson, Luze, Eshbaugh, Jeon, & Kantz, 2007). A self-reflective attitude also leads home visitors to ask families to reflect on how the services are working for them and to make adjustments when families' needs or circumstances change (Bernstein, 2002;DEC, 2014).…”
Section: Attitudes Home Visitors Needmentioning
confidence: 99%
“…Department of Health & Human Services, 2004). For example, some home visitors may have some family-centered attitudes, yet struggle to see their role as one of promoting positive parenting instead of as one who teaches the child themselves-a far less effective practice (Bruder, 2010;Campbell & Sawyer, 2007Fleming, Sawyer, & Campbell, 2011;Hebbeler & Gerlach-Downie, 2002;Peterson, Luze, Eshbaugh, Jeon, & Kantz, 2007). A self-reflective attitude also leads home visitors to ask families to reflect on how the services are working for them and to make adjustments when families' needs or circumstances change (Bernstein, 2002;DEC, 2014).…”
Section: Attitudes Home Visitors Needmentioning
confidence: 99%
“…With the shift from pull-out, child-focused interventions (Fleming et al, 2011;Peterson et al, 2007;Salisbury & Cushing, 2013) to situated coaching and embedded intervention for infants and toddlers approach within the classroom schedule of activities, future research questions are wide ranging. Given the preliminary success of this approach, it would make sense to replicate with teachers of similar backgrounds but with added supports to help teachers implement the strategies as consistently as possible.…”
Section: Future Directionsmentioning
confidence: 99%
“…Survey data gathered by the Center to Inform Personnel Preparation Policy and Practice in Early Intervention and Preschool Education (2007) indicated that most states report that EI professionals across disciplines are not adequately trained to provide family-centered services and supports. When interviewed about participation-based services, most EI providers did not describe two key components of recommended practice in EI: (a) use of the family's routines and activities as the intervention context and (b) EI providers' role to coach caregivers to embed intervention in these routines (Fleming, Sawyer, & Campbell, 2011). Related research substantiates that the adoption and use of coaching is limited and challenging for EI providers to implement (Campbell & Sawyer, 2007;Peterson, Luze, Eshbaugh, Jeon, & Kantz, 2007;Salisbury, Woods, & Copeland, 2010).…”
mentioning
confidence: 99%